Modern Requirements for Future Elementary Technology Education Teachers - Kuttibekova Guljan Tulepbaevna; Jo‘raboeva Dilnoza Suyunovna (Zien Journals, 2023)
Scientific and methodological work on developing the competence of prospective teachers to receive information involves integrating information-related subjects with public science, creating integrated programs and textbooks.
Keywords: school; curriculum; vocational education